Resistance of Vibrio cholera to antibiotics that inhibit cell wall synthesis: A systematic review and meta-analysis - Nateghizad, Hossein; Sajadi, Rojina; Shivaee, Ali; Shirazi, Omid; Sharifian, Mohadeseh; Tadi, Danyal Abbasi; Amini, Kumarss (Frontiers in Pharmacology, 2023)
Objective: Cholera is a challenging ancient disease caused by Vibrio cholera (V. cholera). Antibiotics that prevent cell wall synthesis are among the first known antibiotic groups. Due to its high consumption, V. cholera has developed resistance to the majority of antibiotics in this class. Resistance to recommended antibiotics for the treatment of V. cholera has also increased. In light of the decrease in consumption of certain antibiotics in this group that inhibit cell wall synthesis and the implementation of new antibiotics, it is necessary to determine the antibiotic resistance pattern of V. cholera and to employ the most effective treatment antibiotic. Method: An comprehensive systematic search for relevant articles was conducted in PubMed, Web of Science, Scopus, and EMBASE through October 2020. Stata version 17.1 utilized the Metaprop package to execute a Freeman-Tukey double arcsine transformation in order to estimate weighted pooled proportions. Results: A total of 131 articles were included in the meta-analysis. Ampicillin was the most investigated antibiotic. The prevalence of antibiotic resistance was in order aztreonam (0%), cefepime (0%), imipenem (0%), meropenem (3%), fosfomycin (4%), ceftazidime (5%), cephalothin (7%), augmentin (8%), cefalexin (8%), ceftriaxone (9%), cefuroxime (9%), cefotaxime (15%), cefixime (37%), amoxicillin (42%), penicillin (44%), ampicillin (48%), cefoxitin (50%), cefamandole (56%), polymyxin-B (77%), carbenicillin (95%) respectively. Discussion: Aztreonam, cefepime, and imipenem are the most efficient V. cholera cell wall synthesis inhibitors. There has been an increase in resistance to antibiotics such as cephalothin, ceftriaxone, amoxicillin, and meropenem. Over the years, resistance to penicillin, ceftazidime, and cefotaxime, has decreased.